2021
DOI: 10.1002/anie.202016995
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Cycloparaphenylenes with a Rigid Aromatic Linker

Abstract: Dimeric cycloparaphenylene (CPP) architectures with well-defined flipping motion are constructed taking advantage of an efficient cyclocondensation reaction. Variable-temperature nuclear magnetic resonance (VT-NMR) analyses and theoretical calculations indicate rapid interconversion of cis and trans conformers at room temperature, while energetically favorable trans conformer exists at low temperature with the metastable cis conformer hidden. The trihexylsilylethynyl-substituted dimer exhibits bright emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 56 publications
2
30
0
2
Order By: Relevance
“…Moreover, the negative cooperativity (4 K 2 / K 1 <1) phenomenon revealed that the binding of the first equivalent PCBM decreases the rate of subsequent binding, which presumably results from the change of electronic effect after the first binding. A similar observation was also reported in two fullerene‐based supramolecular complex [13c] . Further studies of the mechanism and the solid‐state structures will be meaningful for supramolecular chemistry.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, the negative cooperativity (4 K 2 / K 1 <1) phenomenon revealed that the binding of the first equivalent PCBM decreases the rate of subsequent binding, which presumably results from the change of electronic effect after the first binding. A similar observation was also reported in two fullerene‐based supramolecular complex [13c] . Further studies of the mechanism and the solid‐state structures will be meaningful for supramolecular chemistry.…”
Section: Methodssupporting
confidence: 83%
“…Other examples incorporating 9,9'-bicarbazole, 9,9'-spirobifluorene, or fused polycyclic aromatic scaffold subunits have been recently synthesized and investigated. [13] Benzene is an aromatic molecule that possesses many representative structures and properties of aromaticity, such as substantial energy stabilization, planarity, bond length equalization, and typical spectroscopic features. [14] Intriguingly, the benzene exhibits conformational ring flexibility and chemical stability even if it suffers severe distortion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These molecular systems, in their cis-conformation, can be regarded as nitrogen-doped nanotube fragments. 27…”
Section: Synpacts Synlettmentioning
confidence: 99%
“…Notably, CPP-PP represents a fully p-conjugated hydrocarbon framework made of 158 sp 2 -carbon atoms as a novel member of CPP architectures that feature multiple nanoring cycles. [23][24][25][26][27] The pivotal intermediate in our synthetic strategy was nanoring 1 (Scheme 1), formed by one dihydrophenalenone unit and 11 phenylene rings. It was synthesized via Suzuki-Miyaura cross-coupling macrocyclization of dihydrophenalenone 2 and C-shaped linker 3.…”
mentioning
confidence: 99%